Digital hyperconnectivity and technostress in faculty at the Universidad Privada de Huancayo Franklin Roosevelt, 2023 - Zavala Figueroa , Nataly Johanna (2024)
Objective: To determine the levels of digital hyperconnectivity and technostress in faculty members of the Universidad Privada de Huancayo Franklin Roosevelt. Material and Methods: A basic descriptive study was conducted with a convenience sample of 86 faculty members. Results: The average age of the faculty members was 47 years old, with 51.2% being male. The most common communication hours were "anytime" (38.4%), and the most commonly used communication methods were WhatsApp and virtual meetings. Regarding frequency of connection outside of work hours, 51.2% reported connecting "frequently," and 34.9% reported completing tasks outside of work hours during "dead time." The dimensions of technostress were as follows: Anxiety: Low level (43%), Fatigue: Low level (41.9%), Skepticism: Low level (48.8%), Inefficacy: Low level (47.7%), Intrapersonal conflicts: Moderate level (45.3%), Emotional exhaustion: Low level (46.5%), Stress: Moderate level (41.9%), The overall level of technostress was low (36%). Conclusions: The study found evidence of digital hyperconnectivity among faculty members, as evidenced by the wide variety of digital communication methods used and the lack of restrictions on communication hours by students. Regarding technostress, 32.6% of faculty members reported a high level, 31.4% reported a moderate level, and 36% reported a low level. The levels of the seven dimensions of technostress ranged from 20% to 33%, suggesting that faculty members are a vulnerable population to technostress due to digital hyperconnectivity.